The Budget Role In Determining Rates For Balangan District Health Center Services: THE BUDGET ROLE IN DETERMINING RATES FOR BALANGAN DISTRICT HEALTH CENTER SERVICES - Yusri, Yusri; Wulandari, Agustina (Program Studi Akuntansi Universitas Islam Lamongan, 2024)
The Budgeting or preparing a good budget is important in managing a health center. A well-planned budget can run community health center operations effectively and efficiently. This research has a high level of urgency because it will provide an understanding of the influence of budgeting and ability to pay in determining service rates at Community Health Centers. This information is important for local governments, health institutions and the community in developing policies that support the accessibility and sustainability of health services in the Balangan Regency area. Qualitative methods are used to obtain an accurate picture of the influence of budgeting and ability to pay in determining service rates, namely using observational data collection techniques, interviews with relevant stakeholders and reviewing documents. Determining rates for Puskesmas services in the Balangan Regency area is greatly influenced by the budget allocated for operational activities and health services, the patient's financial capabilities, budgeting and the patient's ability to pay interact with each other in determining service rates